Network+ fast pass - Ferguson, Bill (Sybex, 2005)
Network+ Fast Pass is the streamlined tool you need to hone in on the Network+ exam. The accompanying CD-ROM lets you practice, practice, practice, and you'll keep the book--packed with concise, objective-focused coverage and review questions--at your side until the minute you sit down to take the test